(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines methodological approaches to developing pragmatic competence in English language teaching for tourism students. It focuses on the importance of equipping learners with the ability to use language appropriately in professional and intercultural contexts, where effective communication is essential. The study analyzes the integration of communicative language teaching, taskbased learning, and content-based instruction as key methodological frameworks for fostering pragmatic skills. Particular attention is given to the role of authentic materials, simulation-based tasks, and roleplay activities in creating realistic communicative environments. These methods enable learners to practice speech acts, apply politeness strategies, and adapt language according to situational demands. The article also highlights the significance of intercultural awareness in avoiding communication breakdowns in tourism settings. The findings suggest that a systematic and integrative methodological approach enhances pragmatic competence and prepares students for effective professional interaction in the global tourism industry.